P03.04.B Garcin syndrome and hippocampal-sparing WBRT: successful resolution of a rare case. (5th September 2022) - Bonzano, E; Russo, R; Colombo, S; Francia, A; Di Liberto, R; Filippi, A
Abstract: Background: first case of a rare Garcin syndrome resolution in a young metastatic breast cancer(BC) patient treated with a hippocampal-sparing approach. Material and Methods: we report a case of a 49-year-old caucasian female. The medical record review was relevant for BC diagnoses in 1997, when she was 26yo; complicated by bone and liver metastasis appeared in 2008. In March 2020, she was referred to our department complaining about increasingly worsening left otalgia with initial hearing loss, left facial numbness, and homolateral decreased facial sensitivity, left increased lacrimation, and tingling tongue. Clinical presentation was suggestive for a Guillain-Alajouanine-Garcin Syndrome (Garcin Syndrome), caused by a lytic lesion in the left sphenoid wing. A contrast MRI (02/04/2020) of the brain demonstrated a lytic lesions in the left sphenoid wing, that was noted to infiltrate surrounding bone of the sphenoid sinus wall, including clivus, left pterygoid process and petrous bone; two parietal and occipital bone lesions were identified with a partial leptomeningeal involvement. According to the good PS, she underwent to a hippocampal-sparing WBRT VMAT plus a sequential boost on sphenoid lesion. PTV and OARs were delineated according to a fused planning MRI/CT image. Bilateral hippocampal contours were generated on the set according to RTOG 0933 contouring atlas. After that, a hippocampal avoidance(HA) region was created by expanding the hippocampal contours by 5 mm in all directions according to Brown et al.The PTV-HA was defined as the WB parenchyma, meninges and skull, excluding the HA-region, dose prescription 30Gy/10fx; the PTV-Boost was defined as the sphenoidal metastases, dose prescription of sequential boost was 12Gy/4fx. VMAT was used to deliver the conformal RT plan. Planning priorities that should be followed were:Hippocampus, OpticChiasm, OpticNerve_L or OpticNerve_R, Lens_L or Lens_R. Results: The neurological symptoms improved after the end of RT with a complete resolution two months later. At the last MRI, a year and a half from the end of RT, there was no evidence of brain lesion, and no neurological symptoms were referred. These are our results of plan sum: for PTV-HA D2%=43.43 Gy, D98%=26.36 Gy, V30=94.96%; for Hippocampus D100%=8.78 Gy, Dmax=17.24 Gy; for Left OpticNerve Dmax=33.51%; for Right OpticNerve Dmax=29.25%; for OpticChiasm Dmax=35.93%. Conclusion: To our knowledge, this is the first described case using the VMAT technique to spare the hippocampus plus a boost in a rare case of Garcin Syndrome. Prevention of neurocognitive sequelae by hippocampal avoidance has shown promise in several studies as in this case. Sequential boost demonstrated to be feasible and effective.Advanced RT techniques may be used to customize a treatment that allows preserving cognitive impairment achieving good clinical results in the long-term survival of metastatic patients.